Ellerines and African Bank : suitable suitors? (A) - Kodongo, Odongo; Berg, Helen van den; Beswick, Claire (London : Wits Business School, 2015)
At the end of the third quarter of 2007, Leon Kirkinis, chief executive officer (CEO) of African Bank Investments Limited (ABIL), unexpectedly arrived at the head office of Ellerine Holdings Limited (EHL), a South African furniture retail group, with a proposal to purchase EHL. For some time, EHL, which derived a substantial portion of its profit from loans provided to customers wishing to buy furniture, had been looking to enter into a deal with a bank as a means of growing its business. Up until the ABIL offer, EHL had been seriously considering a joint venture with Capitec Bank. Now, EHL's CEO, Peter Squires, and the EHL board had to decide which route to choose.
Originally published in Kodongo, O., van den Berg, H., & Beswick, C. (2015). Ellerines and African Bank: Suitable Suitors? (A). WBS-2015-9. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kirkinis, Leon; Squire, Peter; African Bank Investments; Ellering Holdings Limited (EHL); Capitec Bank; Consolidation and merger of corporations -- Africa -- Case studies